Design UWB antenna with notch band for WiMAX application - Alaa Mohsen Ali; ِAli Khalid Jassim (Institute of Advanced Engineering and Science, 2023)
During the last two decades, radar, remote sensing, and imaging applications have all made use of ultra-wide band (UWB) technology. UWB systems are susceptible to interference from narrowband signals, hence this work provides a single-notch antenna for the UWB system. There are two stages to the design process. After creating the baseband antenna, it is necessary to create a notched band UWB antenna by carving a slot into patch antenna. In the UWB range (3.1-10.6) GHz, the UWB antenna has the dimensions of 20x30 mm with substrate thickness 1.6 mm made from FR4 lossy. The design relative permittivity was 4.3, a rectangular patch with a portion of the ground is used in the design. A typical slot-shaped resonator is connected to the patch to reject a frequency band (3.273-3.81) GHz which is a world interoperability for microwave access (WiMAX) to solve the problem of the interference with other bands in UWB system For WiMAX applications. The suggested UWB filter will achieve notch band response centered at the resonance frequency of 3,4 GHz. Analysis CSTS v2020 software was used to carry out the simulation. Priority should be given to what has been learned rather than what has been accomplished.